2014
DOI: 10.1016/j.patrec.2013.04.028
|View full text |Cite
|
Sign up to set email alerts
|

Robust gender recognition by exploiting facial attributes dependencies

Abstract: Estimating human face gender from images is a problem that has been extensively studied because of its relevant applications. Recent works report significant drops in performance for state-of-the-art gender classifiers when evaluated "in the wild," i.e. with uncontrolled demography and environmental conditions. We hypothesize that this is caused by the existence of dependencies among facial demographic attributes that have not been considered when building the classifier. In the paper we study the dependencies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
43
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 24 publications
1
43
0
2
Order By: Relevance
“…testing with an independent dataset, whose images were captured with different conditions. Crossdatabase classification is closer to real situations with no dataset bias, that has been proven to provoke optimistic accuracies [7,19]. Indeed, in real scenarios a gender classifier is trained with a set of images, and later deployed under conditions that may differ from those of the training dataset.…”
Section: Related Workmentioning
confidence: 99%
“…testing with an independent dataset, whose images were captured with different conditions. Crossdatabase classification is closer to real situations with no dataset bias, that has been proven to provoke optimistic accuracies [7,19]. Indeed, in real scenarios a gender classifier is trained with a set of images, and later deployed under conditions that may differ from those of the training dataset.…”
Section: Related Workmentioning
confidence: 99%
“…Sekara and Lehmann [29] studied how to deploy the electronic datasets as a valid proxy for real life social interactions, and found that the strength of electronic signals can be used to distinguish between strong and weak friendship ties. Some other information has been used to predict users' demographics: predicting authors' age and gender from their writing styles [30]; gender classification from videos analysis [31]; and gender/age estimation from images of faces [32,33]. Due to the scope of this study, we will not detail existing research in this direction.…”
Section: Social Behaviormentioning
confidence: 99%
“…Juan Bekios-Calfa, Jose m.Buenaposada and Luis Baumela [8], studied the problem of gender recognition from a multiattribute perspective. Gender recognition under constrained conditions (e.g.…”
Section: Figure 1 Typical Framework For Gender Classification Systemmentioning
confidence: 99%